PENGARUH PENDIDIKAN AGAMA ISLAM DAN POLA ASUH ORANG TUA DEMOKRATIS TERHADAP AKHLAK REMAJA DI LINGKUNGAN MASYARAKAT SUMBER DESA SUMBER MULYO KECAMATAN JOGOROTO KABUPATEN JOMBANG - Abidatul Madliyah; Muhtadi; Abdul Rouf (Arsy : Jurnal Studi Islam, 2020)
This study aims to determine the relationship between Islamic religious education and democratic parenting with adolescent morals .The subjects of this study were 79 adolescents who were in the Sumbermulyo village, Jogoroto district, Jombang district. To obtain data on the relationship between Islamic religious education and democratic parenting and adolescent morals, a questionnaire prepared by the researcher was used. To achieve this goal, the data were analyzed by regression analysis, as well as by observation and some existing data and documents.The results of this study indicate that there is a very significant positive correlation between the relationship between Islamic Religious Education and democratic parenting patterns with adolescent morals in the Sumbermulyo village, Jogoroto district, Jombang district.